2007
DOI: 10.1103/physrevlett.98.225901
|View full text |Cite
|
Sign up to set email alerts
|

Fast Interfacial Ionic Conduction in Nanostructured Glass Ceramics

Abstract: The hopping movements of mobile ions in a nanostructured LiAlSiO4 glass ceramic are characterized by time-domain electrostatic force spectroscopy (TDEFS). While the macroscopic conductivity spectra are governed by a single activation energy, the nanoscopic TDEFS measurements reveal three different dynamic processes with distinct activation energies. Apart from the ion transport processes in the glassy and crystalline phases, we identify a third process with a very low activation energy, which is assigned to io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 15 publications
2
43
0
1
Order By: Relevance
“…Below room temperature, the Arrhenius fit yields an activation energy of 0.04 and 0.08 eV for the two investigated samples, which indicate ionic movements at the interfaces with activation energies of only a few times k B T [32]. This result for the interfacial activation energy clearly shows that the interfacial areas do not form percolating pathways through the glass ceramic.…”
Section: Nanostructured Solid Ion Conductorsmentioning
confidence: 49%
“…Below room temperature, the Arrhenius fit yields an activation energy of 0.04 and 0.08 eV for the two investigated samples, which indicate ionic movements at the interfaces with activation energies of only a few times k B T [32]. This result for the interfacial activation energy clearly shows that the interfacial areas do not form percolating pathways through the glass ceramic.…”
Section: Nanostructured Solid Ion Conductorsmentioning
confidence: 49%
“…suggested that the fast ionic conduction of mobile ions in nanostructured LiAlSiO 4 glass ceramics is caused by the local movement of ions at the interfaces between the glassy phase and embedded crystallites. The existence of an electrical relaxation process with a very low activation energy, which is absent in pure LiAlSiO 4 glass, has been demonstrated by time-domain electrostatic force spectroscopy 18 . Actually, we observed the formation of a nanocrystalline phase in the diffraction pattern after the annealing, which means that the Bragg peaks were deformed, as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is known that the interfacial region between two oxides possesses high excess free energies which would lead to rich structural defects and changes in lattice position. 36,37 The interface strain effects and the influences of grain sizes and grain orientations are negligible in our multilayer. It has been reported that the activation energy for hopping oxygen vacancy in electrolyte would be lowered by disordered interfacial microstructures.…”
Section: Resultsmentioning
confidence: 95%